DECOLORIZATION OF TEXTILE DYES WITH CRUDE LIGNINOLYTIC ENZYMES FROM Coriolopsis caperata - Agnestisia, Retno; Karelius, Karelius; Oksal, Efriyana; Nion, Yanetri Asi (BRIN - Badan Riset dan Inovasi Nasional, 2025)
The textile industry is a major contributor to global water pollution, releasing an estimated 280,000 tons of synthetic dyes annually into aquatic ecosystems. These dyes, particularly azo compounds, are often toxic, mutagenic, and resistant to conventional wastewater treatment methods. Microbial enzymatic degradation, especially by white-rot fungi, offers a promising eco-friendly alternative. This study aimed to optimize the production of ligninolytic enzymes—Laccase (Lac), manganese peroxidase (MnP), and lignin peroxidase (LiP)—from Coriolopsis caperata, and assess their efficiency in degrading two azo dyes: Reactive Red 21 (RR21) and Reactive Orange 107 (RO107). The fungus, isolated from the Peat Swamp Forest in Sebangau, Central Kalimantan, was cultured in a modified glucose-peptone medium enriched with veratryl alcohol. The optimization parameters included variations in time, dye concentration, and the addition of hydrogen peroxide (H₂O₂). Enzyme activity was quantified spectrophotometrically, and dye decolorization was assessed over time at different dye concentrations. Among the enzymes, Lac showed the highest activity (4938.05 U/L), followed by LiP (995.26 U/L) and MnP (246.47 U/L). These values notably exceed several previously reported benchmarks for fungal enzyme activity. RO107 demonstrated greater susceptibility to enzymatic degradation, with 83.71% decolorization achieved at 24 hours, while RR21 reached 65.71% at 48 hours. The addition of 1 mM H₂O₂ significantly enhanced decolorization, increasing RR21 and RO107 removal to 95.71% and 99.30%, respectively. These results underscore the oxidative synergy between H₂O₂ and ligninolytic enzymes, particularly LiP and MnP. Overall, the study demonstrates the potential scalability of C. caperata-based enzymatic treatment systems for textile effluent bioremediation, supporting compliance with environmental discharge regulations and contributing to sustainable wastewater management.